2013
DOI: 10.1007/s00253-013-4724-1
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induced by copper oxide quantum dots in cultured C2C12 cells via caspase 3 and caspase 7: a study on cytotoxicity assessment

Abstract: We report herein the synthesis and characterization of copper oxide quantum dots and their cytotoxic impact on mouse C2C12 cells. The utilized CuO quantum dots were prepared by the one-pot wet chemical method using copper acetate and hexamethylenetetramine as precursors. The physicochemical characterization of the synthesized CuO quantum dots was carried out using X-ray diffraction, energy-dispersive X-ray analysis, and transmission electron microscopy. To examine the in vitro cytotoxicity, C2C12 cell lines we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…[22] The method was explained in detail in our previous article. [21] The relative quantification ratios were obtained following the equation as described by Pfaffl.…”
Section: Methodsmentioning
confidence: 99%
“…[22] The method was explained in detail in our previous article. [21] The relative quantification ratios were obtained following the equation as described by Pfaffl.…”
Section: Methodsmentioning
confidence: 99%
“…The higher the levels of caspase-3, the lower the number of surviving cells [Sandri et al, 2001;Liu et al, 2009;Amna et al, 2013]. We next evaluated apoptosis biochemically by semiquantifying the levels of caspase-3.…”
Section: Effect Of Mechanical Stretch On the Expression Of Caspase-3 mentioning
confidence: 99%
“…Chemical methods using chemical substances, cationic liposomes, cell penetrating peptides (CPPs), and antibodies were found to be useful for labeling QDs. 15,[38][39][40][41] Octa-arginine (R8) peptide was particularly readily available for stem cell labeling in our studies, because of the low cytotoxicity, easy operation and short transduction time. QDs with a negatively charged surface and R8 peptide were complexed at an optimum concentration ratio for 15 min, and then the solution including QDs and R8 complexes was added to the cell culture medium.…”
Section: Qd Types and Stem Cell Labeling Strategies Using Qdsmentioning
confidence: 99%
“…35 Sugaya et al has generated internalizing QDs (i-QDs) by conjugating the particles with an internalizing antibody against mortalin, a heat shock protein 70 family stress chaperone. 38 Zhao et al demonstrated that H178 phage can specifically bind to human embryonic stem cells (hESCs) in vitro using QDs conjugated to the H178 phage ( Fig. 2b).…”
Section: Qd Types and Stem Cell Labeling Strategies Using Qdsmentioning
confidence: 99%